Host records of Physocephala wulpi Camras, with a description of the puparium (Diptera: Conopidae) - Stuke, Jens-Hermann; Lucia, Mariano; Abrahamovich, Alberto H. (Zootaxa, 2011)
Physocephala wulpi Camras was reared from Xylocopa artifex Smith, Xylocopa augusti Lepeletier, and Xylocapa splendidula Lepeletier. The puparium is described. An overview of conopid host records from the Neotropic Region, and records from Conopidae that develop in Xylocopa, is provided.